simplify and write in exponential form p²×p-7
Attachments:
![](https://hi-static.z-dn.net/files/dd4/37cdee99fee244019a84e3392d62c002.jpg)
bhailalbhoi4:
hi
Answers
Answered by
3
Answer:
Step-by-step explanation:
i)
p^-2*p^-7 =
1/p^9
mark me as brainliest
mark me as brainliest
mark me as brainliest
mark me as brainliest
Answered by
3
a²-b²+2bc-c² =a² - (b² -2bc +c²)
=a² - (b-c)²
=(a-(b-c))(a+(b-c))
[ using identity a²-b² =(a-b)(a+b) ]
= (a-b+c)(a+b-c)
hence.,a²-b²+2bc - c² = (a-b+c)(a+b-c)
Similar questions